Fate of Tableted Freeze-Dried siRNA Lipoplexes in Gastrointestinal Environment - Asad Ur Rehman; Virginie Busignies; Marcela Coelho Silva Ribeiro; Nayara Almeida Lage; Pierre Tchoreloff; Virginie Escriou; Christine Charrueau (MDPI AG, 2021)
The incorporation of siRNA into nanocarriers is mandatory to facilitate its intracellular delivery, as siRNA itself cannot enter cells. However, the incorporation of these nanocarriers into oral, solid dosage forms and their fate in the gastrointestinal environment is yet to be explored. In the present work, the fate of, (i) naked siRNA, (ii) freshly prepared siRNA lipoplexes, and (iii) tableted siRNA lipoplexes, in simulated gastric and intestinal fluids was studied. The siRNA, either released from or protected within the lipoplexes, was quantified by gel electrophoresis and siRNA efficacy was assessed in cell transfection. The freshly prepared lipoplexes kept their siRNA load and transfection efficiency totally preserved during 1 h of incubation in simulated gastric fluid at 37 °C. However, in simulated intestinal fluid, despite no release of siRNA from lipoplexes after 6 h of incubation, gene silencing efficacy was dramatically decreased even after 1 h of exposure. The lipoplexes obtained from tablets efficiently protected siRNA in simulated gastric fluid, thus preserving the gene silencing efficacy, whereas their incubation in simulated intestinal fluid resulted in a marked siRNA release and decreased gene silencing efficacy. These results provided a detailed explanation for understanding the fate of siRNA in gastrointestinal conditions, when simply loaded in lipoplexes or formulated in the form of tablets.